A report on practice in industry training in fish technology. - Lope, Belina L. (College of Fisheries, University of the Philippines, 1978)
This report is about the on-the-job training I have undergone at different fish processing plants, submitted in partial fulfillment of the requirements in our course. The knowledge we learned enabled me to apply in actual the theoretical knowledge we learned from school. In addition I have come to know the different practices in the industry as well as the problems encountered. The apprenticeship was full of happy and sad experience, sometimes moments of fatigue. Nevertheless, we were able to have the chance to mingle with the people, the owners and the laborers. The training and observation were carried out at the following fish processing plants: Oval international, Ltd. Leleng's patis factory Conchita Corpuz smoking plant With this experience, I have acquired an actual working know-how of fish preservation. This could be of great help in the near future.